Semantic Analysis of Figurative Language in Miguel's "Sure Thing" - Annisa Rahmawati; Aulia Fatekhah Putri; Otto V. Siregar (Jurnal Inovasi Global, 2025)
In this case, we have discussed song lyrics or poetry. Therefore, we chose one of Miguel's songs titled 'Sure Thing'. This provides a deep insight into how Miguel uses language to convey stories, messages, and emotions in his work. The research we analyze this time is the lyrics of Miguel's song 'Sure Thing'. The purpose of this semantic analysis research is to find out the meaning of each word and provide so that we can practice the role of each diction in communication accompanied by learning about semantics. The method used in this research is qualitative method. Based on the results of the research, 5 Metaphors, 2 imagery, 1 Simile, 3 Symbolism, 1 Personification, 1 Repetition, and 2 Alliteration were found. The total result of figurative language is 13. The reason that is the subject of this analysis is to identify and interpret the use of personification, metaphor, simile, hyperbole, and other forms of figurative language in the lyrics. Imagery and figurative language are approaches used to analyze a literary work in order to understand and explore the literary structure contained in the lyrics. Be it poetry, prose, novels, short stories, or drama. In this case, we have discussed song lyrics or poetry. Therefore, we chose one of Miguel's songs entitled 'Sure Thing'. It provides a deep insight into how Miguel uses language to convey stories, messages, and emotions in his work.